Metallicity and X-ray luminosity variations in NGC 922. Issue 1 (23rd October 2020) - Kouroumpatzakis, K; Zezas, A; Wolter, A; Fruscione, A; Anastasopoulou, K; Prestwich, A
ABSTRACT: We present a systematic study of the metallicity variations within the collisional ring galaxy NGC 922 based on long-slit optical spectroscopic observations. We find a metallicity difference between star-forming regions in the bulge and the ring, with metallicities ranging from almost solar to significantly sub-solar ($\rm {[12+\log (O/H)]\sim 8.2}$ ). We detect $\rm{He\, {\small I}}$ emission in all the studied regions of the bulge and the ring, indicating ionization from massive stars associated with recent (<10 Myr) star formation, in agreement with the presence of very young star clusters. We find an anticorrelation between the X-ray luminosity and metallicity of the sub-galactic regions of NGC 922. The different regions have similar stellar population ages, leaving metallicity as the main driver of the anticorrelation. The dependence of the X-ray emission of the different regions in NGC 922 on metallicity is in agreement with similar studies of the integrated X-ray output of galaxies and predictions from X-ray binary population models.